Sequence-dependent mechanical, photophysical and electrical properties of pi-conjugated peptide hydrogelators1. Issue 25 (7th July 2015) - Ardoña, Herdeline Ann M.; Besar, Kalpana; Togninalli, Matteo; Katz, Howard E.; Tovar, John D.
<x xml:space="preserve">Abstract</x> An investigation of how systematic variation of peptide sequence influences the nanoscale and bulk properties of 1D-nanostructure forming peptide–π–peptide hydrogelators is reported herein.